Bacillus cereus - Eglezos, S.; Dykes, Gary (2014)
© 2014 Elsevier Ltd. All rights reserved. Bacillus cereus food poisoning is the general description of illness associated with this organism, although two recognized types of illness are caused by two distinct metabolites (toxins). The diarrheal type of illness is caused by a large-molecular-weight protein and the vomiting (emetic) type of illness is associated with cereulide, an acid- and heat-resistant polypeptide. Bacillus cereus is member of a group of closely related organisms, the B. cereus complex. Work aimed at understanding the relationships between members of the complex, and on their characteristics and mechanisms of pathogenicity, has been extensive. The occurrence of these organisms in foods and the means by which they can be controlled are considered in this article.